Application of 3D Printing-Assisted Articulating Spacer in Two-Stage Revision Surgery for Periprosthetic Infection after Total Knee Arthroplasty: A Retrospective Observational Study. (8th February 2021) - Kong, Lingtong; Mei, Jiawei; Ge, Wufei; Jin, Xiansheng; Chen, Xiaoxuan; Zhang, Xianzuo; Zhu, Chen
Abstract : Background . Bone cement spacers are widely used in two-stage revision surgeries for periprosthetic joint infection (PJI) after total knee arthroplasty. Current spacer design results in insufficient release of drugs; therefore, current spacers have low efficacy. In this study, we explored a set of alternative articular spacer using 3D printing technology. This novel spacer will increase effectiveness of revision surgery for PJI. Methods . The spacer was designed using CAD software and constructed on site using 3D-printed silicone mold during debridement surgery. We carried out a retrospective study among patients undergoing treatment using traditional static and new articular spacers. Infection control rate, bone loss, difficulty of revision surgery, knee joint range of motion, function evaluation, and subjective satisfaction of the patients in the two groups were compared. Results . Forty-two patients undergoing knee revision surgery between Jan 2014 and Nov 2019 were included in this study. Twenty-two patients were treated with static antibiotic cement spacers, whereas the other twenty patients were with treated with 3D printing-assisted antibiotic loaded articulating spacers. Patients in the articular group showed significantly lower bone loss on the femur site and tibial site compared with patients in the static group. In addition, patients in the articular group showed significantly less operation time, intraoperative blood loss, and improved knee function and patient overall satisfaction compared with patients in the static group. Conclusions . The 3D printing-assisted articular spacer provides satisfactory range of motion during the interim period, prevents bone loss, facilitates second-stage reimplantation and postoperative rehabilitation, and results in low reinfection and complication rates.